EXISTENTIALIST MODEL OF REALITY IN THE WORKS OF UKRAINIAN WRITERS OF THE EARLY 20th CENTURY - Malyshivska, I. V.; Trotsenko, O. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article reads about national peculiarities of existentialist model of reality in the works of such Ukrainian writers as V. Pidmogylnyy, Y. Pluzh-nyk, and M. Hvylovyy. The attention is paid to such key existentialist concepts as loneliness, alienation, freedom, absurdity. It is worth mentioning that the existentialist ideas of Ukrainian writers are based on the philosophical works of G. Skovoroda and P. Yurkevych.